Ankle Joint Contact Loads and Displacement With Progressive Syndesmotic Injury. (September 2015) - Hunt, Kenneth J.; Goeb, Yannick; Behn, Anthony W.; Criswell, Braden; Chou, Loretta
Background: Ligamentous injuries to the distal tibiofibular syndesmosis are predictive of long-term ankle dysfunction. Mild and moderate syndesmotic injuries are difficult to stratify, and the impact of syndesmosis injury on the magnitude and distribution of forces within the ankle joint during athletic activities is unknown. Methods: Eight below-knee cadaveric specimens were tested in the intact state and after sequential sectioning of the following ligaments: anterior-inferior tibiofibular, anterior deltoid (1 cm), interosseous/transverse (IOL/TL), posterior-inferior tibiofibular, and whole deltoid. In each condition, specimens were loaded in axial compression to 700 N and then externally rotated to 20 N·m torque. Results: During axial loading and external rotation, both the fibula and the talus rotated significantly after each ligament sectioning as compared to the intact condition. After IOL/TL release, a significant increase in posterior translation of the fibula was observed, although no syndesmotic widening was observed. Mean tibiotalar contact pressure increased significantly after IOL/TL release, and the center of pressure shifted posterolaterally, relative to more stable conditions, after IOL/TL release. There were significant increases in mean contact pressure and peak pressure along with a reduction in contact area with axial loading and external rotation as compared to axial loading alone for all 5 conditions. Conclusion: Significant increases in tibiotalar contact pressures occur when external rotation stresses are added to axial loading. Moderate and severe injuries are associated with a significant increase in mean contact pressure combined with a shift in the center of pressure and rotation of the fibula and talus. Clinical Relevance: Considerable changes in ankle joint kinematics and contact mechanics may explain why moderate syndesmosis injuries take longer to heal and are more likely to develop long-term dysfunction and, potentially, ankle arthritis.